Utility of Pulse Oximetry Oxygen Saturation (SpO2) with Incorporation of Positive End-Expiratory Pressure (SpO2∗10/FiO2∗PEEP) for Classification and Prognostication of Patients with Acute Respiratory Distress Syndrome - Pratibha Todur; Anitha Nileshwar; Souvik Chaudhuri; Nitin Gupta; Srikant Natarajan; Shwethapriya Rao (Critical Care Research and Practice)
Background. Conventionally, PaO2/FiO2 (P/F ratio) has been used to categorize severity of acute respiratory distress syndrome (ARDS) and prognostication of outcome. Recent literature has shown that incorporation of positive end-expiratory pressure (PEEP) into the P/F ratio (PaO2∗10/FiO2∗PEEP or P/FP∗10) has a much better prognostic ability in ARDS as compared to P/F ratio. The aim of this study was to correlate SpO2∗10/FiO2∗PEEP (S/FP∗10) to PaO2∗10/FiO2∗PEEP (P/FP∗10) and evaluate the utility of S/FP∗10 as a reliable noninvasive indicator of oxygenation in ARDS to avoid repeated arterial blood sampling. Aim. To evaluate if pulse oximetry is a reliable indicator of oxygenation in ARDS patients by calculating SpO2∗10/FiO2∗PEEP (S/FP∗10). The primary objective was to determine the correlation of S/FP∗10 to P/FP∗10 ratio in ARDS patients. The secondary objective was to determine the cut-off value of S/FP∗10 ratio to predict severe ARDS and survival. Methods. Patients aged 18–80 years on invasive mechanical ventilation (MV) diagnosed with ARDS as defined by the Berlin definition were included. The values of PaO2, FiO2, and SpO2 were collected at three different time points. They were at baseline, i.e., after intubation and initiation of MV (within one hour of intubation), day one (1–24 hours of MV), and day three (48–72 hours of MV). The primary outcome was survival at the end of intensive care unit (ICU) stay. Results. A total of 85 patients with ARDS on invasive MV were included. The data points were obtained at baseline, day one, and day three of MV. S/FP∗10 ratio has an excellent correlation to P/FP∗10 ratio at baseline and day three of invasive MV (r = 0.831 and 0.853, respectively; p<0.001) and has a strong correlation on day one of invasive MV (r = 0.733, p<0.001). S/FP∗10 ratio ≤116 at baseline has excellent discriminant function to be categorized as severe ARDS as per Berlin definition (AUC: 0.925, p<0.001, 90% sensitivity, 93% specificity, CI: [0.862–0.988]). The increase in S/FP∗10 ratio by ≥64.40 from baseline to day three of MV is a good predictor of survival (AUC: 0.877, p<0.001, 73.5% sensitivity, 97% specificity, CI: [0.803–0.952]). Conclusion. S/FP∗10 has a strong correlation to P/FP∗10 in ARDS patients. S/FP∗10 ≤116 has an excellent discriminant function to be categorized as severe ARDS. The S/FP∗10 ratio on day three of MV and the change in S/FP∗10 ratio from baseline and day one to day three of MV are good predictors of survival in ARDS patients. This trial is registered with CTRI/2020/04/024940.